Redescription and phylogenetic position of the poorly known ghost shrimp species, Praedatrypaea modesta (De Man, 1905) (Decapoda: Axiidea: Callianassidae) - Kou, Qi; Poore, Gary C. B.; Li, Xinzheng (Zootaxa, 2026)
A poorly known callianassid ghost shrimp species, Praedatrypaea modesta (De Man, 1905), is redescribed and illustrated based on new material recently collected off the south coast of Hainan Island, northern continental shelf of the South China Sea. Genetic data were obtained and compared with other six congeners. With the inclusion of this species, the monophyly of Praedatrypaea Poore, Dworschak, Robles, Mantelatto & Felder, 2019 is reevaluated. The inferred phylogenetic trees, based on two matrices (4-gene and 21-gene), both support the monophyly of this genus and its placement as sister taxon to all other genera of Callianassidae Dana, 1852.